Random and systematic set-up errors in three-dimensional conformal radiotherapy – impact on planning target volume margins: the experience of the Radiation Oncology Centre of Sassari. Issue 2 (31st May 2013) - Tamponi, Matteo; Poggiu, Angela; Dedola, Maria F.; Madeddu, Rossella; Carnevale, Antonella; Manca, Gianfranca; Tola, Rossana; Bona, Rossana; Carai, Alessandro; Fundoni, Carla; Naitana, Alessandra; Giordani, Nella; et al.
Abstract Purpose Geometric uncertainties limit the accuracy of three-dimensional conformal radiotherapy treatments. This study aims to evaluate typical random and systematic set-up errors and analyse the impact of no action level (NAL) correction protocol on systematic set-up errors and clinical target volume (CTV)–planning target volume (PTV) margins. Materials and methods A total 668 pairs of orthogonal electronic portal images were compared with digitally reconstructed radiographs from computed tomography planning scans for 100 patients consecutively treated during 2011. Patients were divided into groups depending on the treated anatomical region. Patient-specific and population random and systematic set-up errors were calculated. Impact of application of NAL correction protocol on systematic set-up errors and CTV–PTV expansions were evaluated. Results Population set-up errors resulted from about 1 mm in head and neck to 2–3 mm in prostate, rectum, lung, breast and gynaecological districts. Patient-specific systematic set-up errors were higher for breast and gynaecological districts and application of NAL correction protocol gave significant reductions, even higher than 30%. Calculated CTV–PTV margins ranged from 10 mm on left–right direction for prostate to 20 mm on superior–inferior direction for lung. Conclusions Set-up errors resulted reasonably controlled and application of NAL correction protocol could further improve the level of accuracy. However, the NAL application alone did not seem to add any substantial benefit on CTV–PTV total margins without the adoption of corrective strategies to reduce other important uncertainties limiting accuracy of three-dimensional conformal radiotherapy.